2008 Symposium on Haptic Interfaces for Virtual Environment and Teleoperator Systems 2008
DOI: 10.1109/haptics.2008.4479994
|View full text |Cite
|
Sign up to set email alerts
|

Force-Feedback Surgical Teleoperator: Controller Design and Palpation Experiments

Abstract: In this paper, we develop and test a 6-degree-of-freedom surgical teleoperator that has four possible modes of operation: (1) direct force feedback, (2) graphical force feedback, (3) direct and graphical force feedback together, and (4) no force feedback. In all cases, visual feedback of the environment is provided via a head-mounted display. A position-position controller with local dynamic compensators provides the direct force feedback. The graphical force feedback is overlaid on the environment image, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…Many experts believe that high-quality haptic feedback (forces and/or tactile sensations) will help surgeons quickly learn and adeptly perform robot-assisted minimally invasive procedures, e.g., [4,10,15,16]; however, the best method for providing this feedback remains unclear due to the wide variety of approaches being explored and the disparate requirements of the surgical tasks being studied. Furthermore, there are many technical challenges associated with adding haptic feedback to telerobotic MIS.…”
Section: Prior Approachesmentioning
confidence: 99%
“…Many experts believe that high-quality haptic feedback (forces and/or tactile sensations) will help surgeons quickly learn and adeptly perform robot-assisted minimally invasive procedures, e.g., [4,10,15,16]; however, the best method for providing this feedback remains unclear due to the wide variety of approaches being explored and the disparate requirements of the surgical tasks being studied. Furthermore, there are many technical challenges associated with adding haptic feedback to telerobotic MIS.…”
Section: Prior Approachesmentioning
confidence: 99%
“…epidural anesthesia, brain biopsy, electrode placement for deep brain stimulation) the surgeon cannot see the path of the needle inside the tissue and thus must rely on his limited sense of touch or on a pre-planned path based on preoperative medical images. Enhancing the perception of the force at the needle/tissue interface could drastically increase the success of needle-based procedures [2]- [4]. The choice of which interaction force is displayed to the operator may have a significant impact on performance.…”
Section: Introductionmentioning
confidence: 99%
“…One study found that incorporating force feedback into surgical simulators enhanced the users performance during more complicated tasks [6]. Other studies have found incorporating force feedback minimizes * jrcoope4@mail.usf.edu † mwernke@mail.usf.edu ‡ kylereed@usf.edu error over graphical force feedback or no force feedback during a palpation task [7]. As these systems develop, the possibilities grow.…”
Section: Introductionmentioning
confidence: 99%